Effect of compound kushen injection on immune function in patients with colorectal cancer: a systematic review and meta-analysis - Zhang, Lixin; Wei, Guangyan; Wang, Kaiping; Han, Xu (Frontiers in Pharmacology, 2025)
BackgroundColorectal cancer (CRC) is one of the most common malignant tumors worldwide. Chemotherapy and radiotherapy remain cornerstone treatments; however, they often lead to significant immune suppression and an increased risk of infection. Enhancing immune function in CRC patients is critical for improving clinical outcomes and prognosis.ObjectiveTo evaluate the effects of Compound Kushen Injection (CKI) on immune function and its role in mitigating chemotherapy-induced adverse effects in patients with CRC.MethodsWe retrieved randomized controlled trials (RCTs) evaluating the effects of CKI on immune function in patients with CRC from eight Chinese and English databases, up until 31 December 2024. The Cochrane Handbook was used to assess the quality of the included studies. For the meta-analysis, we utilized Review Manager 5.4.1 software. Sensitivity analysis and publication bias assessment were conducted using Stata 17.0 software.ResultA total of 2,663 patients (1,550 males and 1,113 females) from 30 RCTs were included. Compared to conventional chemotherapy (CC), the combination of CKI with CC significantly enhanced immune function, increasing CD3+ levels (MD = 6.15, 95% CI: 4.78 to 7.53, p < 0.00001), CD4+ levels (MD = 8.05, 95% CI: 6.99 to 9.11, p < 0.00001), CD4+/CD8+ levels (MD = 0.36, 95% CI: 0.28 to 0.44, p < 0.00001), NK cell levels (MD = 3.60, 95% CI: 2.85 to 4.34, p < 0.00001), while reducing CD8+ levels (MD = −4.19, 95% CI: −5.11 to −3.27, p < 0.00001). CKI also improved the objective response rate (ORR, RR = 1.50, 95% CI: 1.38 to 1.62, p < 0.00001) and disease control rate (DCR, RR = 1.15, 95% CI: 1.10 to 1.19, p < 0.00001), decreased CEA levels (MD = −1.79, 95% CI: −2.81 to −0.76, p = 0.0007) and CA199 levels (MD = −0.73, 95% CI: −1.35 to −0.12, p = 0.02), and reduced chemotherapy-induced adverse reactions, including nausea, vomiting, hepatic dysfunction, myelosuppression, neurotoxicity, leukopenia, thrombocytopenia, and mouth ulcers.ConclusionCurrent evidence suggests that the combination of CKI with CC may have beneficial effects on immune function, ORR, DCR, and chemotherapy-induced adverse reactions in CRC patients. However, given the variability in study quality and the absence of disease stage stratification, these findings should be interpreted with caution. Furthermore, the lack of long-term follow-up data limits the understanding of CKI’s impact on survival and quality of life. High-quality, large-scale RCTs with extended follow-up are needed to further assess the long-term efficacy, safety, and clinical applicability of CKI in CRC management.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=632516, identifier CRD42025632516